Implications of Population Growth: Islamic and Social Perspectives (Al-Qamar, 2018)
There are pertinent factors that are causing the multiplication of human beings and various implications of the immense growth. This study discussing population growth and its implications, points out the social responsibility and Islamic guidelines in this regard. It concludes that according to Islamic teachings, family size can be negotiated and planned by married couples. Many Islamic teachings are either not read properly, interpreted correctly or conveyed with true spirit. Educated religious scholars understand and elaborate the real issues associated with unchecked population growth. From social perspective, it is being observed that high level of illiteracy, lack of true religious knowledge and poverty are contributing to the many detrimental consequences such as high maternal and infant mortality rates, malnourishment of children, less or no investment in children’s education etc.. On macro level, growing food insecurity, environmental degradation, unemployment, solid waste and poor hygienic conditions are among the few not to be ignored.
Keywords: Population; Family planning; Islam; Social attitudes